The Absence of God in Biblical Rape Narratives - Schulte, Leah Rediger (Book collections on Project MUSE., 2017)
In this groundbreaking work to identify and address God's absence in three key rape narratives in the Hebrew Bible, Leah Rediger Schulte finds a pattern that indicates a larger community crisis. With a careful look at Genesis 34, Judges 19, and 2 Samuel 13, this study outlines God's absence, a foreign presence, and a persistent problem that is resolved incorrectly to highlight consequences of the Israelites breaking their covenant with God.